Methanol‐to‐Olefins in a Membrane Reactor with in situ Steam Removal – The Decisive Role of Coking. Issue 1 (25th November 2019) - Rieck genannt Best, Felix; Mundstock, Alexander; Dräger, Gerald; Rusch, Pascal; Bigall, Nadja C.; Richter, Hannes; Caro, Jürgen
Abstract: The reaction of methanol to light olefins and water (MTO) was studied in a fixed bed tubular membrane reactor using commercial SAPO‐34 catalyst. In the fixed bed reactor without membrane support, the MTO reaction collapsed after 3 h time on stream. However, if the reaction by‐product steam is in situ extracted from the reactor through a hydrophilic tubular LTA membrane, the reactor produces long‐term stable about 60 % ethene and 10 % propene. It is shown that the reason for the superior performance of the membrane‐assisted reactor is not the prevention of catalyst damage caused by steam but the influence of the water removal on the formation of different carbonaceous residues inside the SAPO‐34 cages. Catalytically beneficial methylated 1 or 2 ring aromatics have been found in a higher percentage in the MTO reaction with a water removal membrane compared to the MTO reaction without membrane support. Abstract : The Methanol‐to‐Olefins (MTO) reaction was performed in a membrane reactor with in situ steam removal through on tubular LTA zeolite membrane, where it showed exceptional long‐term stability over 4 hours, while maintaining a stable product distribution. Further examination showed a different coking behavior as the reason for the improvement compared to a fixed bed reactor without membrane support.